MENINGKATKAN AKTIVITAS DAN KETUNTASAN BELAJAR KIMIA MELALUI PENERAPAN PEMBELAJARAN KOOPERATIF NUMBERED HEADS TOGETHER (NHT) PADA SISWA KELAS XI IPA 7 SMAN 1 PEKANBARU - Halbi, Zulfira; M. Noer, Asmadi; Erviyenni, Erviyenni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstrak: This classroom action research aims to improve the activity and students learning result in chemistry on class XI IPA 7 of SMAN 1 Pekanbaru by applying cooperative model of Numbered Heads Together (NHT). There were 33 students of XI IPA 7 SMAN 1 Pekanbaru involved in study that did in three cycles of learning. Each cycle consisted of one meetings through four stages of implementation: planning, action, observation, and reflection. Data collection techniques using observation and test. The result of action showed that total activity percentage of students increased and reached the success indicator with 62,2% students were active in three cycles. Total activity of student percentage in first cycle 57,7% with criteria enough, second cycle 60,5% with criteria enough and three cycle 68,3% with criteria good. The average percentage of mastery learning classical also increased and reached the success indicator with 78,8% in three cycle. The average percentage in first, second and third cycle followed by 51,7%, 78,1% dan 81,8%.Keyword : Cooperative model of NHT, Student Activities, Mastery Learning Classical